Dynamic measurement of centering forces on transvalvular cannulas. Issue 4 (11th December 2019) - Stoiber, Martin; Aigner, Philipp; Grasl, Christian; Röhrich, Michael; Moscato, Francesco; Schima, Heinrich
Abstract: In heart failure therapy, minimally invasive devices (transcatheter valves, catheter‐based cannulas or pumps) are increasingly used. The interaction with the valve is of special importance as valve damage, backflow, and thrombus formation are known complications. Therefore, the aim of this in vitro study was to characterize the forces acting on different sized transvalvular cannulas at various transvalvular pressures for four different valves. In a pulsatile setup radial and tangential forces on transvalvular cannulas were measured for bioprosthetic, artificial pericardial tissue, fresh, and fixated porcine valves. The cannula position was varied from a central position to the wall in 10° rotational steps for the whole circular range and the use of different cannula diameters (4, 6, and 8 mm) and transvalvular pressures (40‐100 mmHg). Centering forces of four different aortic valve types were identified and the three leaflets were visible in the force distribution. At the mid of the cusps and at the largest deflection the forces were highest (up to 0.8 N) and lowest in the commissures (up to 0.2 N). Whereas a minor influence of the cannula diameter was found, the transvalvular pressure linearly increased the forces but did not alter the force patterns. Centering forces that act on transvalvular cannulas were identified in an in vitro setup for several valves and valve types. Lowest centering forces were found in the commissures and highest forces were found directly at the cusps. At low pressures, low centering forces and an increased cannula movement can be expected.